Atomic oxygen radical‐induced intracellular oxidization of mould spore cells. Issue 10 (8th June 2020) - Tanaka, Yuta; Oh, Jun‐Seok; Hashizume, Hiroshi; Ohta, Takayuki; Kato, Masashi; Hori, Masaru; Ito, Masafumi
Abstract: The inactivation mechanism of mould spores using plasma‐generated neutral reactive oxygen species (ROS) was investigated in this paper. Typical cell viability using a counting of colony‐forming unit assay indicated a major state of the spore cells. Both intracellular and extracellular damages have been investigated by a couple of well‐established cell visualization techniques: confocal fluorescence emission microscopy, scanning electron microscopy, and transmission electron microscopy. It is revealed in this paper that the combination of the spore cell viability with those visualization results strongly suggested an early stage of the cell inactivation when ROS can induce intracellular lipid peroxidation through both nanometer‐thick lipid cell membrane and less‐damaged several hundred nanometer‐thick cell wall. Abstract : The inactivation mechanism of mould spores using plasma‐generated neutral reactive oxygen species (ROS) was investigated in this paper. Typical cell viability using a counting of colony‐forming unit assay indicated a major state of the spore cells. Both intracellular and extracellular damages have been investigated by a couple of well‐established cell visualization techniques: a confocal fluorescence emission microscopy, scanning electron microscopy, and transmission electron microscopy. It is revealed in this paper that the combination of the spore cell viability with those visualization results strongly suggested an early stage of the cell inactivation when ROS can induce intracellular lipid peroxidation through both nanometer‐thick lipid cell membrane and less‐damaged several hundred nanometer‐thick cell wall.